An integrated and comparative approach to genetic selection of the aquaculture species Dicentrarchus labrax - Louro, Bruno (2015)
The European sea bass, Dicentrarchus labrax, is one of the most important marine species cultivated in Southern Europe and has not benefited from selective breeding. One of the major goals in the sea bass (D. labrax) aquaculture industry is to understand and control the complexity of growth associated traits. The aim of the methodology developed for the studies reported in the thesis was not only to establish genetic and genomic resources for sea bass, but to also develop a conceptual strategy to efficiently create knowledge in a research environment that can easily be transferred to the aquaculture industry. The strategy involved; i) establishing an annotated sea bass transcriptome and then using it to, ii) identify new genetic markers for target QTL regions so that, iii) new QTL analysis could be performed and marker based resolution of the DNA regions of interest increased, and then iv) to merge the linkage map and the physical map in order to map the QTL confidence intervals to the sea bass genome and identify genes underlying the targeted traits. Finally to test if genes in the QTL regions that are candidates for divergent growth phenotypes have modified patterns of transcription that reflects the modified whole organism physiology SuperSAGE-SOLiD4 gene expression was used with sea bass with high growth heterogeneity. The SuperSAGE contributed to significantly increase the transcriptome information for sea bass muscle, brain and liver and also led to the identification of putative candidate genes lying in the genomic region of growth related QTL. Lastly all differentially expressed transcripts in brain, liver and muscle of the European sea bass with divergent specific growth rates were mapped to gene pathways and networks and the regulatory pathways most affected identified and established the tissue specific changes underlying the divergent SGR. Owing to the importance of European sea bass to Mediterranean aquaculture and the developed genomics resources from the present thesis and from other studies it should be possible to implement genetic selection programs using marker assisted selection.